Integrated watershed modeling for simulation of spatiotemporal redistribution of post-fallout radionuclides: Application in radiocesium fate and transport processes derived from the Fukushima accidents. (October 2015) - Mori, Koji; Tada, Kazuhiro; Tawara, Yasuhiro; Ohno, Koichi; Asami, Mari; Kosaka, Koji; Tosaka, Hiroyuki
Abstract: Simulation of the watershed-scale fate and transport of radionuclides is required in order to predict the consequences of contamination redistribution. Integrated watershed modeling is a suitable technique for this task, but it requires fully coupled investigation of radionuclide behavior in surface water, suspended sediment and subsurface aquifers. We developed a novel simulator for computing the spatiotemporal redistribution of fallout radionuclides in watersheds. The simulator was applied to an actual reservoir basin contaminated by fallout radionuclides from the Fukushima Dai-Ichi Nuclear Power Plant accident in 2011. As a result, the simulated 137 Cs concentration in bottom sediment showed a reasonably close match with the measurement data. The distribution coefficient of 137 Cs consistent with the latest measurement data was identified as being at least 400, 000 L/kg, and it was estimated that more than 90% of the total 137 Cs distributed in the fallout remains in the catchment area. Highlights: We propose a new simulator to assess environmental impact of fallout radionuclide. Simulation treats surface and subsurface fully coupled hydrological processes. Spatiotemporal variation of the deposited 137 Cs can be successfully reproduced. Deposited 137 Cs is predominantly transported with the suspended sediment. Results indicate that most of the deposited 137 Cs remains within the catchment.